How can health care organisations make and justify decisions about risk reduction? Lessons from a cross-industry review and a health care stakeholder consensus development process. (May 2017) - Sujan, Mark A.; Habli, Ibrahim; Kelly, Tim P.; Gühnemann, Astrid; Pozzi, Simone; Johnson, Christopher W.
Abstract: Interventions to reduce risk often have an associated cost. In UK industries decisions about risk reduction are made and justified within a shared regulatory framework that requires that risk be reduced as low as reasonably practicable. In health care no such regulatory framework exists, and the practice of making decisions about risk reduction is varied and lacks transparency. Can health care organisations learn from relevant industry experiences about making and justifying risk reduction decisions? This paper presents lessons from a qualitative study undertaken with 21 participants from five industries about how such decisions are made and justified in UK industry. Recommendations were developed based on a consensus development exercise undertaken with 20 health care stakeholders. The paper argues that there is a need in health care to develop a regulatory framework and an agreed process for managing explicitly the trade-off between risk reduction and cost. The framework should include guidance about a health care specific notion of acceptable levels of risk, guidance about standardised risk reduction interventions, it should include regulatory incentives for health care organisations to reduce risk, and it should encourage the adoption of an approach for documenting explicitly an organisation's risk position. Highlights: Empirical description of industry perceptions on making risk reduction decisions. Health care consensus development identified five recommendations. Risk concept should be better integrated into safety management. Education and awareness about risk concept are required. Health systems need to start a dialogue about acceptable levels of risk.